KEPEMIMPINAN NASIONAL DAN PERAN MILITER DALAM PROSES DEMOKRATISASI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
In response to a widespread pressure for political reform, the military has abandon its predominant role in Indonesian politics in the past Yet the incompetence of civilian politician to govern a deep and extensive conflict embedded within the process of democratization, paradoxically, has driven the need for inviting a military "came back". While positively supporting the military attempt to be politically impartial, this article itemizes four agendas: (1) for recruiting national leaders which are, on the one hand, democratic, but on the other hand, decisive, (2) engaging in a trust-building process among various factions